The Implications of the Individualism and Communitarian Debate for Civic Education The Task of Democratic Orientation - Duerr, Karlheinz ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
Although the demise of communism in Eastern Europe in 1989 was described as "the ultimate victory of Democracy," this paper asserts that serious internal problems exist within modern democracies throughout Europe and the United States today. However, civic education offers a potential remedy. Part 1, "The New Democratic Question," identifies the main problem area as the relationship between the individual and the community, the so-called "communitarian debate." With the decline of many formerly dominant social institutions (religions organizations, the family, and school) that defined and provided answers to basic moral and ethical questions, the new replacements are often factions and small organizations that offer an almost infinite variety of moral norms, resulting in a new sense of uncertainty, a lack of social and cultural orientation, and a rise in individualism. In Part 2 "The Crisis of Democratic Orientation" is evidenced in the following three societal developments: the decline of central political institutions; the growth in distance between citizen and state; and the rise of special agenda organizations (social movements, interest and lobby groups). These developments represent a change in democratic attitudes resulting in a growing divide between the way democracy works in practice and its normative and legal foundations as set in its constitutions and laws. Part 3, "Implications for Civic Education," proposes that civic education is the best arena in which to ensure that democratic principles are embedded firmly in the social framework of a society and in the hearts and minds of the people. However, a new civic education framework should include expanded methods that reflect social change and the multiplicity of the factors at work in the public sphere. (CB)
ERIC Note: Paper presented at the International Conference on Individualism and Community in a Democratic Society (Washington, DC, October 6-11, 1996).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship; Citizenship Education; Civics; Democracy; Democratic Values; Foreign Countries; Futures (of Society); Individualism; Political Attitudes; Social Change; Values Education; Europe (East); Communitarianism -- Germany; Speeches/Meeting Papers; Reports, Descriptive